Selexipag for the treatment of pulmonary arterial hypertension. (4th May 2021) - Genecand, Léon; Wacker, Julie; Beghetti, Maurice; Lador, Frédéric
ABSTRACT: Introduction: : Pulmonary arterial hypertension (PAH) is a rare pulmonary vasculopathy. This review focuses on selexipag, a prostacyclin receptor agonist validated for the treatment of PAH. Areas covered: We review the structure, mechanisms of action, pharmacokinetics, and pharmacodynamics of selexipag. Clinical efficacy and tolerability are discussed using the main clinical trial published for selexipag (GRIPHON) and its post-hoc analysis. Expert opinion: Selexipag should be added as a triple oral combination therapy in case of insufficient response to oral combination therapy with endothelin receptor antagonist and phosphodiesterase 5 inhibitor. However, selexipag should not replace parenteral prostacyclin in high-risk patients.